The low cost Proton Precession Magnetometer developed at the Indian Institute of Geomagnetism - Mahavarkar, Prasanna; Singh, S.; Labde, S.; Dongre, Varun; Patil, A. (My University, 2017)
Proton magnetometers are the oldest scalar magnetometers. The first commercial units were produced in early 1960s as portable instruments. In continuation airborne instruments appeared with optimized speed of readings and sensitivity, large sensors etc. Later development of Overhauser and optically pumped magnetometers has eliminated Proton magnetometers from airborne surveys. However they remain very popular in various ground surveys and observatories. With this primary purpose of generating the ground based magnetic data, the Indian Institute of Geomagnetism (IIG) for the last 3 decades have been developing low cost Proton Precession Magnetometers (PPM). Beginning with the 1 nT PPM which has undergone several changes in design, the successor PM7 the advanced version has been successfully developed by the institute and is installed at various observatories of the institute. PM7 records the total field ‘F’ with accuracy of 0.1 nT and a sampling rate of 10 seconds/sample. This article briefly discusses the design and development of this IIG make PM7 and compares the data recorded by this instrument with one of the commercially available Overhauser magnetometer in the world market. The quality of data recorded by PM7 is in excellent agreement with the Overhauser. With the available quality of data generated by this instrument, PM7 is an affordable PPM for scientific institutions, schools and colleges intending to carry out geomagnetic studies. The commercial cost of PM7 is 20% of the cost of Overhauser available in market.
Keywords: Manufacturing; Detector design; Construction technologies and materials; PPM; Proton Precession Magnetometer